THE IMPACT OF HYBRID WORKING ON EMPLOYEE PERFORMANCE AND WELL-BEING IN THE DIGITAL ERA - Rosari, Maria Aurelia; Anondo Retno Dewati; Muhammad Calvin; Ratih Febrianti; Nola Febrianty (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2025)
The hybrid work model has become an important phenomenon in the post-pandemic transformation of the world of work, especially in responding to the needs of flexibility and employee well-being in the digital era. The purpose of this activity is to systematically analyze the impact of hybrid working on employee performance and well-being based on a synthesis of current literature. This research uses a Systematic Literature Review (SLR) approach with the PRISMA protocol-based selection method. The partners in this activity were Krisnadwipayana University student groups with a total of five participants. The process was carried out by identifying 45 articles through six databases, then selected to produce 19 articles selected for analysis. The results of the study show that hybrid working has a positive impact on productivity, engagement, work-life balance, and organizational efficiency, but also presents challenges such as digital fatigue, leadership bias, and changes in workplace identity. In conclusion, hybrid working has the potential to be a long-term work solution that supports employee performance and well-being, provided that its implementation must be supported by inclusive organizational policies, adequate technological infrastructure, and supportive and adaptive leadership to the needs of the modern workforce.